(untitled) (Global Journal of Management and Business Research, 2016)
The aim of this study is to investigate the relations between exchange rate, interest rate and producer prices for 2004-2013 periods in Turkey. To the determine relationships between variables Johansen Co-Integration, Vector Error Correction, Granger Causality and Relative Sensitivity Analysis are used. According to results of the study; there are short and long-term relationships between exchange rate, interest rate and producer prices. Beside this, relationship between inflation and the exchange rate is higher than the interest rate. On the other hand, effect of the interest rate on the exchange rate is weak. These results can be interpreted as the interest rate has a low contribution in the production costs compared to that of the exchange rate for Turkey. Therefore, economic policies for stability in the exchange rate can be recommended such as increase in the exchange rate earnings and reducing expenses.